A Multidimensional and Multilevel Examination of Student Engagement and Secondary School Teachers' Use of Classroom Management Practices. (July 2021) - Larson, Kristine E.; Pas, Elise T.; Bottiani, Jessika H.; Kush, Joseph M.; Bradshaw, Catherine P.
Student engagement is a multidimensional construct influenced by complex student, classroom, and school factors. Although prior research has examined various dimensions of student engagement, few studies have adopted a multilevel approach to simultaneously incorporate observational measures of classroom practices with student and school factors. The current study examined the association between student self-reported affective and behavioral engagement ( n = 26, 849 students) and observed instructional and behavioral classroom management practices within 401 classrooms in 54 high schools. We employed three-level hierarchical linear modeling and included student, classroom, and school variables. Results indicated that observed teacher use of positive behavior supports was positively and significantly associated with student reports of active engagement in the same classroom. Implications for improving teachers' classroom management practices to promote student engagement are considered.